Influenza Vaccination: Effectiveness, Indications, and Limits in the Pediatric Population - Mameli, Chiara; Cocchi, Ilaria; Fumagalli, Mara; Zuccotti, Gianvincenzo (Frontiers in Pediatrics, 2019)
Influenza vaccine is considered the most effective way to prevent influenza. Nonetheless, every year vaccine coverage is lower than recommended in the pediatric population. Many factors are supposed to contribute to this phenomenon such as the uncertainty about the indication for vaccination and the suboptimal vaccine-effectiveness in pediatric age, especially in the youngest children. In this review we discuss the effectiveness, indications and limits of influenza vaccination in the pediatric population based on the most recent evidences.